The Council Fathers’ Discussions and Controversies on the Inclusion of References to Islam in the Second Vatican Council Documents - Kościelniak, Krzysztof (Verbum Vitae, 2026)
This article presents a detailed account of the evolution of references to Islam during the Second Vatican Council. Analyses reveal systematic changes, beginning with the Council Fathers’ narrow perspective at the Council’s outset (related to differing interpretations of the principle extra Ecclesiam nulla salus), continuing through preparations for Vatican II and the changes occurring during individual sessions. The dynamics of this process encompassed the activity of Middle Eastern bishops (especially the Melkite hierarchy) and Pope Paul VI, as well as the evolution of texts on Islam in the documents Lumen gentium and Nostra aetate. It is significant that the theology of Louis Massignon, developed in the first half of the 20th century, became an acceptable basis for references to Islam in the Council’s documents. Nevertheless, the path to the official recognition of the necessity of dialogue with Muslims, from the Council’s lack of interest in non-Christian religions to the adoption of references to Islam, was long, difficult, and at the same time fascinating. Finally, in Nostra aetate, the passage on Islam (no. 3) is presented before the mention of Judaism (no. 4). The article shows how these concise Council mentions of Islam—due to their official character, their essentially positive content, and the direction of the Church’s thought and action—ultimately paved a new path for Catholic communities.